2012
DOI: 10.1029/2011ja016976
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of tweeks and nighttime D region ionosphere at tweek reflection height from the observations in the low‐latitude Indian sector

Abstract: , at Allahabad, a low-latitude station in the Indian sector, has been used to study seasonal occurrence which shows maximum tweek occurrence of about 63% during summer season and about 19% and 18% occurrences during equinox and winter seasons. Maximum occurrence of tweeks during summer season is consistent with the larger number of lightnings detected by World Wide Lightning Location Network in the Indian and Asia Oceania regions during summer as compared to that during equinox and winter. Seasonally, tweek (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 66 publications
0
22
1
Order By: Relevance
“…Tweeks occurred on magnetically quiet days and showed day-today variability of up to 8 km under purely nighttime VLF propagation. Our results of h varying from 75 -97 km show that some of the tweeks originating from the dayside would have propagated to our station in contrast to the observations by Maurya et al (2012). This is likely to happen at our station as most of the tweek propagation path is over sea whereas propagation to Indian low latitude stations is mostly over the land which offers higher attenuation (Kumar et al, 2008).…”
Section: Ionospheric D-region Remote Sensing Using Tweekscontrasting
confidence: 53%
See 1 more Smart Citation
“…Tweeks occurred on magnetically quiet days and showed day-today variability of up to 8 km under purely nighttime VLF propagation. Our results of h varying from 75 -97 km show that some of the tweeks originating from the dayside would have propagated to our station in contrast to the observations by Maurya et al (2012). This is likely to happen at our station as most of the tweek propagation path is over sea whereas propagation to Indian low latitude stations is mostly over the land which offers higher attenuation (Kumar et al, 2008).…”
Section: Ionospheric D-region Remote Sensing Using Tweekscontrasting
confidence: 53%
“…However, the variability in f c and hence in h and n e is larger as compared to these authors. Maurya et al (2012) analyzed the tweek data recorded during 2010 at the Indian low latitude stations (Allahabad and Nainital) and showed that D-region electron density varies 21.5 -24.5 cm -3 over the ionospheric reflection height of 85 -95 km. Tweeks occurred on magnetically quiet days and showed day-today variability of up to 8 km under purely nighttime VLF propagation.…”
Section: Ionospheric D-region Remote Sensing Using Tweeksmentioning
confidence: 99%
“…The group velocity v gm in the homogeneous spherical EIWG is given by (Ohya et al 2008;Maurya et al 2012b):…”
Section: Discussionmentioning
confidence: 99%
“…Ohya et al (2011) found that about 67 % of the nighttime D-region ionization is caused by Lyman-α and Lyman-β which ionize NO and O 2 at altitude of 95 km. The lower h in the pre-midnight period during winter as compared to equinox and summer seasons is explained by the fact that the lower n e of daytime during winter giving rise to slower the loss processes of electrons in the pre-midnight period (Maurya et al 2012b). Those phenomena clearly show at lower altitudes of the D-region.…”
Section: Morphology Of Nighttime D-region Ionospherementioning
confidence: 99%
“…Networks of ground‐based ELF/VLF receivers have been deployed over many of the world’s regions, including the Atmospheric Weather Electromagnetic System for Observation, Modeling, and Education (AWESOME) (Cohen et al, 2010; Carpenter et al, 2012), the World Wide Lightning Location Network (WWLLN) (Dowden et al, 2002), and the Antarctic‐Arctic Radiation‐belt (Dynamic) Deposition‐VLF Atmospheric Research Konsortium (AARDDVARK) (Clilverd et al, 2009), to observe natural whistler wave emissions and man‐made VLF transmitter signals. Based upon all these ELF/VLF receiver observation campaigns, much progress has been achieved in the past decade, in particular a number of useful applications in the context of geophysical studies of the ionosphere and magnetosphere, such as radio atmospherics, ionospheric remote sensing, and ELF/VLF generation and detection (e.g., Ohya et al, 2008; Kumar et al, 2009; Yusop et al, 2013; Maurya et al, 2012; Singh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%